Evaluation of new polysaccharides networks for extended-release purposes: mesquite seed gum (MSG), xanthan gum and chitosan (Revista Brasileira de Ciências Farmacêuticas, 2003)
The aim of this work was to design new hydrophilic matrix (HM) systems by cross-linking Mesquite Seed Gum (MSG), a galactomannan that occurs in the endosperm layer of the seeds of a Brazilian tree,Prosopis juliflora DC, with two well-known polysaccharides with the ability of retarding drug release, chitosan and xanthan gum. This had in mind the idea of using these new compounds in the preparation of extended-release dosage oral forms. The first part of this study was dedicated to the evaluation of MSG in terms of its functionality as a hydrophilic matrix (HM) system for extended-release purposes. Next, we started the study of water uptake profile of all polymers of interest (MSG, Xanthan Gum and Chitosan), in the following media: water, SGF and SIF. Following, we searched for the best cross-linking agent between Glutharaldehyde (GA) and Hexamethylenediisocyanate (HMDI), which turned out to be the GA. Next step we begun to prepare new hydrophilic matrices of MSG_Chitosan and MSG_Xanthan Gum, with different ratios, 1:1, 1:2 and 2:1. Finally, after deciding which new HM system presented best results, by using statistics tools, we investigated the mechanism controlling the rate release of the model drug, from tablets made with this new matrix. As a final result we concluded that the best combination of polysaccharides was achieved with MSG and Xanthan Gum, with mass ratio of 1:2, using glutharaldehyde aqueous solution as cross-linking agent. It presented a prevalent zero order kinetics, which is a very important feature when thinking about an extended-release oral dosage.